Involvement of mammalian SoLute Carriers (SLC) in the traffic of polyamines - Pochini, Lorena (Frontiers in Molecular Biosciences, 2024)
Polyamines interact with different molecular targets for regulatingto regulate a vast range of cellular processes. A network of enzymes and transport systems is crucial for the maintenance of polyamine homeostasis. Indeed, polyamines after synthesis must be distributed to the various tissues and some intracellular organelles. Differently from the well characterized enzymes devoted to the polyamine synthesis, the transport systems are not unequivocally identified or characterized. Besides some ATPases which have been identified as polyamine transporters, much less in is known about solute carriers (SLC) involved in the transport of these compounds. Only two SLCs have been unequivocally identified as polyamine transporters: SLC18B1 (VPAT) and SLC22A4 (OCTN1). Transport studies have been performed with cells transfected with the cDNAs encoding the two and other SLCs or, in the case of OCTN1, also by in vitro assay using proteoliposomes harboring the recombinant human proteins. According to the role proposed for OCTN1, polyamines have been associated to with prolonged and quality of life. This review provides an update on the most recent findings concerning the polyamine transporters or the prediction of the putative ones.